BUREAUCRATIC PATHOLOGIES AND EXECUTIVE DEFIANCE IN COASTAL MINING CONCESSIONS: A POLITICAL AND CRIMINAL LAW PERSPECTIVE - Alwi Al Hadad; Litya Surisdani Anggraeniko; Shaifullah (Fakultas Politik Pemerintahan, 2026)
The centralization of electronic mining licensing in Indonesia has given rise to bureaucratic pathologies in the form of sectoral egos that undermine local autonomy and threaten the sustainability of coastal ecosystems. This study aims to deconstruct legal anomalies and political dynamics in governance regarding the issuance of mining operation permits on small islands, analyze the impasse in litigation practices, and formulate a framework for resolving the dysfunction in the execution of administrative court rulings (PTUN). Through a normative legal research method employing legislative, conceptual, and case-based approaches to Supreme Court Decision No. 650 K/TUN/2022, this study identifies three structural flaws. First, the central government’s erroneous application of the lex specialis doctrine has prioritized the mining exploitation regime over imperative instruments for the protection of coastal ecosystems. Second, the absence of enforceable executive instruments within the PTUN procedural law triggers institutional defiance, where decisions to revoke permits become ineffective and merely create an illusion of environmental justice. Third, this systemic weakness is exploited by administrative officials through the manipulation of issuing new disputed objects (permit recycling) to circumvent the court’s ruling. As a solution, this paper recommends a paradigm shift from formal-procedural oversight toward outcome-based governance evaluation. This must be accompanied by the absolute blocking of an integrated geospatial data-based permitting system, as well as the imposition of dwangsom (compulsory fines) directly levied on the personal assets of state officials and the integration of criminal law enforcement against defiant bureaucrats to break the chain of administrative law circumvention. Keywords: Bureaucratic Pathologies; Executive Defiance; Licensing Centralization; Political Dynamics; Criminal Liability.